Rates of Dinitrogen Fixation and the Abundance of Diazotrophs in North American Coastal Waters Between Cape Hatteras and Georges Bank - Hyde, K.; Mannino, A.; Moisander, P. H.; Turk, K.; Mondragon, E.; Mulholland, M.R.; Bernhardt, P. W.; Zehr, J. P.; Blanco-Garcia, J. L. (2012)
We coupled dinitrogen (N2) fixation rate estimates with molecular biological methods to determine the activity and abundance of diazotrophs in coastal waters along the temperate North American Mid-Atlantic continental shelf during multiple seasons and cruises. Volumetric rates of N2 fixation were as high as 49.8 nmol N L(sup -1) d(sup -1) and areal rates as high as 837.9 micromol N m(sup -2) d(sup -1) in our study area. Our results suggest that N2 fixation occurs at high rates in coastal shelf waters that were previously thought to be unimportant sites of N2 fixation and so were excluded from calculations of pelagic marine N2 fixation. Unicellular N2-fixing group A cyanobacteria were the most abundant diazotrophs in the Atlantic coastal waters and their abundance was comparable to, or higher than, that measured in oceanic regimes where they were discovered. High rates of N2 fixation and the high abundance of diazotrophs along the North American Mid-Atlantic continental shelf highlight the need to revise marine N budgets to include coastal N2 fixation. Integrating areal rates of N2 fixation over the continental shelf area between Cape Hatteras and Nova Scotia, the estimated N2 fixation in this temperate shelf system is about 0.02 Tmol N yr(sup -1), the amount previously calculated for the entire North Atlantic continental shelf. Additional studies should provide spatially, temporally, and seasonally resolved rate estimates from coastal systems to better constrain N inputs via N2 fixation from the neritic zone.